Pengaruh Motivasi Intrinsik dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Dinas Lingkungan Hidup Kabupaten Bima - Ayuriati, Ayuriati; Jaenab; Julaiha (Indo-MathEdu Intellectuals Journal, 2026)
Employee performance is an important factor in supporting the effectiveness of public organizations and the quality of services to the public. This study aims to analyze the influence of intrinsic motivation and work environment on employee performance at the Environmental Service of Bima Regency. This study uses a quantitative approach with an associative research type. Intrinsic motivation and work environment act as independent variables, while employee performance is the dependent variable. Data were collected through questionnaires to 58 respondents selected using a purposive sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS, including validity tests, reliability, classical assumptions, coefficient of determination, t-test, and F-test. The results showed that intrinsic motivation did not have a significant effect on employee performance (t = 1.626; p = 0.110), while the work environment had a positive and significant effect (t = 5.550; p < 0.001). Simultaneously, both variables significantly influenced employee performance (F = 47.029; p < 0.001), with a coefficient of determination of 0.631. Thus, improving the quality of the work environment became a more dominant strategy in supporting employee performance improvement, while intrinsic motivation continued to play a supporting role.